Energy harvesting using thermoelectric generator (TEG) for a stand alone led street light - Wan Mohd Zahiruddin bin Wan Mohd Rusdi (2023)
The thesis entitled 'Energy Harvesting Using Thermoelectric Generstor (TEG) for a stand alone LED street light reports, mainly on the procedures, theory, simulating, testing and analyzing the project system using specified programmed software and hardware.